Pengaruh Gaya Kepemimpinan dan Disiplin terhadap Motivasi Kerja Serta Pengaruhnya pada Kinerja Pegawai Dinas Perhubungan Provinsi Jambi Tahun 2023 - Alhudhori, M. (Universitas Batanghari Jambi, 2025)
This research aims to analyze and prove the influence of leadership style and discipline on work motivation and its influence on the performance of Jambi Province Transportation Service employees. Data was collected through questionnaires distributed to 171 people. Apart from questionnaires, data was also collected through short interviews. This research uses a quantitative approach with the analysis techniques used are multiple regression models and path analysis. The research results show that an effective leadership style has a positive effect on employee work motivation. Likewise, high work discipline significantly increases employee motivation. This research also proves that work motivation can act as a mediating variable that strengthens the relationship between leadership style and work discipline on employee performance. In other words, a good leadership style and high work discipline not only have a direct effect on employee performance, but also indirectly through increasing the work motivation of Jambi Province Transportation Service employees.